Uveal Melanoma Metastasis Models - Yang, Hua (Ocul Oncol Pathol, 2015)
Metastatic disease is the leading cause of death among patients with uveal melanoma. Treatment options for patients with clinically disseminated disease are usually unsuccessful. In vitro and in vivo models are important tools to investigate the pathogenesis of metastatic uveal melanomas and develop treatments for the metastases. In vitro experimental approaches focusing on cell invasion/migration which mimic the steps of the complex metastatic process may also be used for the identification of potential anti-invasion/migration drugs that may inhibit the spreading of tumor cells or the development of metastases. The effects of these drugs must subsequently be confirmed in reliable in vivo models before entering the clinical trial phase. Several models of intraocular melanoma with metastases in rodents and rabbits are currently being used. Most experimental models of uveal melanoma metastases require injection or implantation of melanoma cells into orthotopic locations, including into the liver, spleen, tail vein, or the left ventricle of the heart, in order to mimic the metastatic process.